Inhibition of Inflorescence in Mangifera indica Linn. By the Gall-forming Psyllid, Apsrlla cistellata Buckt. (Psyllidae-Homoptera) Control Measures - Chatterjee, P. N.; Sebastian, V. O. (Indian Forester, 1965)
no abstract